Penerapan Alat Pengering Bahan Pangan Sebagai Teknologi Tepat Guna Bagi Umkm - Muhammad Iqbal Suseno Putra; Iqbal Dwi Prayoga; Melkior Aleks Kalvaro; Raissa Dea Fernanda; Wiranata Kusuma Atma Wijaya (Journal of Community Service and Engagement, 2026)
The application of food drying equipment as an appropriate technology for herbal micro, small, and medium enterprises (MSMEs) in Pandanarum Village aims to improve production efficiency, product quality, and business sustainability. This study examines the performance of the drying tool through field implementation, training, and direct observation during the drying process of herbal raw materials such as ginger, turmeric, cinnamon, and temulawak. The findings indicate a significant reduction in drying time, more uniform moisture content, and improved cleanliness, color stability, and aroma compared to traditional sun-drying methods. The use of the drying equipment also enhances production consistency and reduces dependence on weather conditions, allowing MSMEs to better manage production schedules and meet market demand. Furthermore, the technology supports sustainable practices by enabling the utilization of herbal waste as value-added products. Overall, the drying tool demonstrates strong potential as an appropriate, affordable, and easily operated technology that strengthens the competitiveness and long-term viability of herbal MSMEs based on local resources.